IN-VITRO COMPARISON OF MICRO-LEAKAGE BETWEEN NANOCOMPOSITE AND MICROHYBRID COMPOSITE IN CLASS V CAVITIES TREATED WITH THE SELF-ETCH TECHNIQUE - Hussain, Syeda Mahvash; Khan, Farhan Raza (Journal of Ayub Medical College Abbottabad, 2016)
Background: When a light cure composite resin is used to restore a class V lesion, certain stresses are generated at the tooth-restoration interface. If these stresses exceed the bond strength of the restorative material, microscopic gaps are formed which eventually cause micro-leakage at the tooth-restoration interface. The objective of the present study was to compare the micro-leakage values at the tooth-restoration interface using dye penetration method between a Nano filled and a Micro hybrid light cured composite resin in class V cavities using the self-etch technique. Methods: Sixty class V cavities were made coronal to the cemento-enamel junction in the extracted premolars. These were then randomly divided into two study groups. Group A: Self-etch; filled with P-60 (micro-hybrid) n=30. Group B: Self-etch; filled with Z-350 (nano-filled) n=30. Specimens were subjected to thermo-cycling at 5-55 °C±2 °C with a 30 seconds dwell time. After which they were stained with 2% methylene blue. Later, sectioned bucco-lingually and examined using a stereo microscope (magnification X4) at the occlusal, axial and gingival surfaces. Micro-leakage around the tooth-restoration interface was assessed by using the degree of dye penetration in millimetres. Results: There was 100% micro leakage seen at both the occlusal and gingival surfaces when using the P-60 composite. With the Z-350 composite 84% occlusal and 88% of the gingival surfaces exhibited micro-leakage. Conclusions: With respect to micro-leakage in class V cavities, Z-350 was found to be a superior restorative material compared to P-60 on the occlusal surface. Overall, there is no statistically significant difference in the micro-leakage exhibited by the two restorative materials in class V preparations subjected to self-etch protocol. Keywords: Class V lesions; self-etch; nanocomposite and micro-hybrid composite